Effects of working grassland management on lesser prairie-chicken resource selection within home ranges and during dispersal events - Gulick, Christopher Kevin (Kansas State University, 2019)
The lesser prairie-chicken (Tympanuchus pallidicinctus) is a grassland obligate whose decline has been associated with anthropogenic fragmentation and land use change. Historical habitat drivers (i.e., natural fires and free roaming grazers) created vegetation heterogeneity across the species’ range, providing resources for each of their life stages. Currently, most of the lesser prairie-chicken’s eastern range consists of rangelands managed with confined continuous livestock grazing without fire as a disturbance. Lesser prairie-chicken habitat is also fragmented at larger scales, limiting dispersals and threatening genetic connectivity. A need exists to determine optimum landscape management that provides seasonal habitat at small scales, and allows for dispersal and metapopulation connectivity at large scales. My first objective was to determine the relationship between cattle distributions and lesser prairie-chicken habitat among patch-burn and rotationally grazed rangelands. My second objective was to determine differences in seasonal selection by female lesser prairie-chickens, relative to fine-scale cattle distributions on these two rangelands. My final objective was to determine movement patterns and resource selection of lesser prairie-chickens during dispersal. I tracked cattle (Bos taurus) and lesser prairie-chickens via satellite telemetry in patch-burn and rotationally grazed pastures to model their space use at fine scales. I estimated vegetation change along the resulting gradient of cattle distributions. I determined seasonal selection of lesser prairie-chickens relative to cattle distributions within each management treatment. I tracked GPS-tagged lesser prairie-chickens in the Mixed-Grass Prairie and Short-Grass Prairie/CRP Mosaic ecoregions and delineated dispersals. I used step selection analysis to determine differences in resource selection along each dispersal route. Year-of-fire patches drove cattle site-selection on patch-burn grazed rangelands, which created greater vegetation heterogeneity within pastures. Lesser prairie-chickens selected for different cattle densities during different life stages. On rotationally grazed pastures, lesser prairie-chickens selected for moderate cattle densities during breeding, moderate-to-high densities during post-breeding, and selected for the greatest fine-scale cattle densities during nonbreeding. Within the patch-burn grazed treatment, females avoided moderate cattle densities during breeding and post-breeding, and selected for the lowest cattle densities during nonbreeding. Patch-burn grazed pastures were more heterogeneous and contained greater forb abundance in areas with low cattle densities, which could create better brooding and post-breeding habitat near nesting habitat. In the Mixed-Grass Prairie Ecoregion, lesser prairie-chickens selected for lower tree densities and increased grassland cover at the landscape scale during dispersal. On the Short-Grass Prairie Ecoregion, lesser prairie-chickens avoided areas containing electrical transmission lines. During dispersal, young females traveled further and took longer movement steps. Successful dispersals were also shorter distances than failed dispersals. Drivers of dispersal may be innate and could occur regardless of annual variation in local habitat; however, there is likely a fitness cost associated with increased dispersal length. Land-use alterations influenced habitat within home ranges and affected population connectivity by altering dispersals. Managers can benefit lesser prairie-chickens by altering grazing management to mimic historical drivers of habitat. Population connectivity could be increased by limiting electrical transmission line establishment along corridors in the Short-Grass Prairie Ecoregion and by removing trees and increasing grassland within the Mixed Grass-Prairie Ecoregion.
Keywords: lesser prairie-chicken; patch-burn grazing; rangeland management; dispersal; step selection